The older persons' assessment and liaison team ‘OPAL’: evaluation of comprehensive geriatric assessment in acute medical inpatients - Harari, D.; Martin, F. C.; Buttery, A.; O'Neill, S.; Hopper, A. (Age and ageing, 2007)
Background: reducing hospital length of stay (LOS) in older acute medical inpatients is a key productivity measure. Evidence-based predictors of greater LOS may be targeted through Comprehensive Geriatric Assessment (CGA). Objective: evaluate a novel service model for CGA screening of older acute medical inpatients linked to geriatric intervention. Setting: urban teaching hospital. Subjects: acute medical inpatients aged 70+ years. Intervention: multidisciplinary CGA screening of all acute medical admissions aged 70+ years leading to (a) rapid transfer to geriatric wards or (b) case-management on general medical wards by Older Persons Assessment and Liaison team (OPAL). Methods: prospective pre-post comparison with statistical adjustment for baseline factors, and use of national benchmarking LOS data. Pre-OPAL (n = 46) and post-OPAL (n = 49) cohorts were similarly identified as high-risk by the CGA screening tool, but only post-OPAL patients received the intervention. Results: pre-OPAL, 0% fallers versus 92% post-OPAL were specifically assessed and/or referred to a falls service post-discharge. Management of delirium, chronic pain, constipation, and urinary incontinence similarly improved. Over twice as many patients were transferred to geriatric wards, with mean days from admission to transfer falling from 10 to 3. Mean LOS fell by 4 days post-OPAL. Only the OPAL intervention was associated with LOS (P = 0.023) in multiple linear regression including case-mix variables (e.g. age, function, ‘geriatric giants’). Benchmarking data showed the LOS reduction to be greater than comparable hospitals. Conclusion: CGA screening of acute medical inpatients leading to early geriatric intervention (ward-based case management, appropriate transfer to geriatric wards), improved clinical effectiveness and general hospital performance.